CHALLENGING ORTHODOXIES: TERRITORIAL INNOVATION POLICIES IN PERIPHERAL REGIONS - SANTOS, Domingos; Maria João Simões (ENTREPRENEURSHIP AND PERFORMANCE IN A REGIONAL CONTEXT_ 24º Workshop da APDR, 2016)
Innovation has been assuming a growing role in regional policy over the past three decades. Public policies have been shaped by "best practice models" associated with new technologies and successful urban-metropolitan areas. However, the knowledge obtained from these examples are rarely transferable to other territorial contexts. The reflection on the regional policy role based on the promotion of the innovation potential in peripheral regions with structural development problems has been relegated to a secondary plan. The main objective of this article is precisely, first, to discuss this issue in the light of the mainstream theoretical frameworks that enable a better understanding of the relationship innovation-territory, analyzing, also, the main criticisms those approaches are arising among some researchers. Finally, the paper discusses the challenging reconfiguration modern territorial innovation policies have to address in the promotion of peripheral least favored regions competitiveness. Peripheral low density regions with structural development problems need basically to avoid tecnopolitan drifts and other misconceptions associated with the fads of the ready-made recipes, rethinking their competitive positioning and finding new formulas that allow improving their insertion patterns into the modern knowledge economy and global flows. We must no longer consider territorial innovation policy as a mere process of resource allocation and spatial design; it should be understood as a set of strategies and instruments that encompasses pedagogical and experimental dimensions that favor the creation of resources and new wealth. Today there is a wide consensus about the fact that the competitive success of the territories rests less on the traditional economic and geographical determinisms than on the socio-political capacity of initiative and organization - is not an easy challenge, but, as paradoxical as it may seem, it is an excellent auspice for peripheral regions.